PENGARUH PEMBERIAN EKSTRAK KUNYIT PUTIH (Curcuma zedoaria) DAN TEMULAWAK (Curcuma xanthorriza) TERHADAP BERAT POTONG, BERAT KARKAS DAN PERSENTASE KARKAS - Renasti Ritonga; Tabita Ralahalu; Dominggus Malle (MARSEGU : Jurnal Sains dan Teknologi, 2025)
The purpose of this study was to determine the effect of giving white turmeric (Curcuma zedoaria) and curcuma (Curkuma xhantorriza) extracts on slaughter weight, carcass weight, and broiler carcass percentage. This research was carried out for 3 months, June – August 2024 in the housing unit of the Maluku Provincial Development Agricultural Vocational High School.  The study used an experimental method with a Complete Random Design (RAL), which included a simple pattern with 4 treatments and 4 replicates. Each replicate consists of 6 chickens. The treatment used was P0= without white turmeric and temulawak treatment (control), P1= 60 mL of white turmeric and temulawak extract, P2= 80 mL of white turmeric and temulawak extract, P3= 100 mL of white turmeric and temulawak extract. The variables studied in this study include feed consumption, drinking water consumption, slaughter weight, carcass weight, and carcass percentage in broilers . Based on the results of this study, the addition of white turmeric extracts (Curcuma zedoaria) and curcuma (Curcuma xanthorrhiza) showed that the P3 treatment had a real effect on the slaughter weight, and the P2 and P3 treatments had a real effect on the carcass weight. Thus, the hypothesis that 80 ml of white turmeric extract and curcuma will affect the weight of broiler carcass is acceptable.